Hubungan Kecanduan Smartphone, Self-Esteem, dan Jenis Kelamin dengan Kecemasan pada Siswa di SMAN 1 Mataram - Perdana, Made Krisna Wahyu; Syuhada, Irwan; Santosa, Hilda; Imam, Lalu Yogi Prasetio (Universitas Malahayati, 2025)
ABSTRACT The World Health Organization (WHO) states that anxiety is a common mental health disorder with a very high prevalence rate. According to the Basic Health Research (Riskesdas) conducted by the Ministry of Health in 2018, emotional disorders among adolescents increased from 6% in 2013 to 9.8% in 2018. Objective to determine the relationship between smartphone addiction, self-esteem, and gender with anxiety among students at SMAN 1 Mataram. This study employed a quantitative, observational analytic approach with a cross-sectional design. The sampling technique used was stratified random sampling. The study was conducted at SMAN 1 Mataram in October 2024, involving a total of 102 respondents. Data were analyzed using the chi-square test with a significance level of p < 0.05. The bivariate analysis revealed a significant relationship between smartphone addiction and anxiety (p-value 0.001), no significant relationship between self-esteem and anxiety (p-value 0.879), and a significant relationship between gender and anxiety (p-value 0.032). There is a significant relationship between smartphone addiction and gender with anxiety, while no significant relationship was found between self-esteem and anxiety among students at SMAN 1 Mataram. Keywords: Smartphone Addiction, Self-Esteem, Gender, Anxiety ABSTRAK World Health Organization (WHO) menyatakan bahwa kecemasan adalah gangguan kesehatan jiwa yang umum dengan tingkat prevalensi yang sangat tinggi. Berdasarkan hasil Riset Kesehatan Dasar (Riskesdas) dari Kementerian Kesehatan (2018), gangguan emosi pada remaja meningkat dari 6% pada tahun 2013 menjadi 9,8% pada tahun 2018. Tujuan penelitian mengetahui hubungan kecanduan smartphone, self esteem, dan jenis kelamin dengan kecemasan pada siswa di SMAN 1 Mataram. Penelitian kuantitatif analitik observasional dengan desain penelitian cross sectional. Teknik pengambilan sampel menggunakan stratified random sampling. Penelitian dilakukan di SMAN 1 Mataram pada bulan Oktober 2024. Sampel penelitian sebanyak 102 responden. Hasil analisis bivariat menunjukkan ada hubungan signifikan kecanduan smartphone dengan kecemasan dengan p-value 0,001, tidak terdapat hubungan signifikan self esteem dengan kecemasan dengan p-value 0.879 dan ada hubungan signifikan jenis kelamin dengan kecemasan dengan p-value 0,032. Terdapat hubungan signifikan kecanduan smartphone dan jenis kelamin dengan kecemasan, dan tidak terdapata hubungan signifikan self esteem dengan kecemasan pada siswa di SMAN 1 Mataram. Kata Kunci: Kecanduan Smartphone, Self Esteem, Jenis Kelamin, Kecemasan